Critical Periods of Storage of the Greenhouse Gases in Polypropylene Syringe - Rigon, João Paulo Gonsiorkiewicz [UNESP] (2017)
It is convenient to store gas samples containing e.g. carbon dioxide (CO2), methane (CH4), and nitrous oxide (N2O), in polypropylene syringes before chromatographic analysis. However, there is no study of the integrity of these samples or of what storage condition may be critical. To investigate we filled polypropylene syringes with two standard mixtures of CO2, CH4, and N2O, and stored them at ~2 °C and ~25 °C, and analyzed the contents using gas chromatography. Our results suggest that the storage of gases on the syringe at room temperature is not viable due the CO2 storage integrity when in low concentration. However, the quantitative integrity of samples is maintained when the syringe is kept refrigerated up to 19 h, period limited by CO2 and CH4, taking into account the three gases CO2, CH4, and N2O.